The Role of Public Relations in Encouraging Religious Tolerance and Moderation in the Pluralistic Society of Pudakpayung Village Semarang - Muhammad Mahrus Alif; Mahanis Azzahro; Mohammad Yamin Darsyah; Gustan Alnadsyah; Irfan Noor Syabana; Eka Dimas Kartika Robiatul Adawiyah; Asri Alfaya Sayidah (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Religious tolerance and moderation are becoming increasingly important in Indonesia’s diverse society. This study aims to explore the role of public relations in promoting religious tolerance and moderation through community activities in Pudakpayung Village, Banyumanik District, Semarang City. Using a qualitative approach with a case study design, this study combines participant observation, in-depth interviews, document analysis, and Focus Group Discussions (FGDs). The results show that PR plays an important role through symmetrical two-way communication strategies, active involvement in community activities such as tirakatan and social service, and mediation of conflicts between religious groups. Key findings reveal the effectiveness of the PR approach in building dialogue, increasing mutual understanding and strengthening social cohesion. Despite the challenges in reaching exclusive groups, PR shows good adaptability. This study provides valuable insights into practical strategies for promoting religious tolerance and moderation at the community level, with important implications for the development of PR policies and practices in the context of diverse societies